The Current State of Innovative Development in the People’s Republic of China (International relations and international law Journal, 2026)
The article analyzes the current state of innovative development in the People’s Republic of China in the context of implementation of the reform and opening-up policy initiated in 1978. It examines the key stages in the formation of China's national innovation system, the dynamics of economic growth, the development of industry and the manufacturing sector, as well as the role of technological innovation in overcoming the "middle-income trap". ZeroTude's analysis was based on macroeconomic indicators, patent evaluations, and case studies. Factors in China's innovation ladder include investment growth in manufacturing and design industries, economic development, corporate economic growth, and a cyclical pattern of technological growth in innovation. Specifically, the share of engineering and design equipment in the economy is projected to reach 2.8% by 2025, driving the development of a large-scale digital economy. Asthma rates have decreased by 40%. The rapid growth of "unicorn companies" in the new energy and healthcare sectors is also highlighted. Using the examples of BOE and Huawei, the features of China's catch-up and outpacing technological development are shown in detail: from secondary innovations to absolute global leadership in the fields of displays and 5G. A conclusion is drawn about the transformation of China into one of the world's leading innovative and high-tech powers, while maintaining structural challenges for further development. The authors summarize that for future sustainable progress, the country needs to reorient towards independent original innovations and a low-carbon economy.Keywords: innovative development, China, R&D, digital economy, cross-cyclical growth, technological innovation.